Review articleEpidermal growth factor receptor in glioblastoma - Żawrocki, Antoni; Biernat, Wojciech (Folia Neuropathologica, 2005)
We compiled the current state of knowledge about the epidermal growth factor receptor (EGFR) in glioblastoma. Glioblastoma is one of the most common primary brain tumours and has an unfavourable prognosis despite aggressive treatment. These factors stimulate new research trials and a recent area of interest of neurooncologists is EGFR. This molecule is frequently altered in glioblastoma and constitutes the potential target for therapy. We decided to review the literature on biological structure of that molecule, its biological activity and the role in GBL with potential targeting it in the future neurooncological practice.